New Technologies, Old Questions: The Enduring Issues of Communications Research. Issue 1 (3rd April 2018) - Golding, Peter
Abstract : Technological change in communications and media has been substantial and dramatic in recent years, particularly arising from the growth of the internet and "social media." This can lead analysis to give undue emphasis to technological innovation at the expense of the enduring patterns of social structure which lie behind them. This article stresses the importance of such continuities by briefly illustrating the importance of power, inequality, identity and social change in relation to communications processes and institutions.